2007
DOI: 10.1007/s11120-007-9194-9
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectroscopy of the manganese cluster of photosystem II

Abstract: Electron paramagnetic resonance (EPR) spectroscopy is a valuable tool for understanding the oxidation state and chemical environment of the Mn4Ca cluster of photosystem II. Since the discovery of the multiline signal from the S2 state, EPR spectroscopy has continued to reveal details about the catalytic center of oxygen evolution. At present EPR signals from nearly all of the S-states of the Mn4Ca cluster, as well as from modified and intermediate states, have been observed. This review article describes the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
127
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 108 publications
1
127
0
Order By: Relevance
“…For example, the S 3 state parallel mode EPR signal (Matsukawa et al 1999) and the g = 4.1 perpendicular mode S 2 state EPR signal (for review see, Haddy 2007) cannot be observed in presence of methanol or ethanol, while in PSII membrane fragments from higher plants the S 0 multiline signal can only be resolved after methanol addition (Messinger et al 1997a). An ESEEM study employing 2 H-labeled methanol clearly showed that methanol (and ethanol) binds at-or at least very close to-the Mn 4 O x Ca cluster (Force et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the S 3 state parallel mode EPR signal (Matsukawa et al 1999) and the g = 4.1 perpendicular mode S 2 state EPR signal (for review see, Haddy 2007) cannot be observed in presence of methanol or ethanol, while in PSII membrane fragments from higher plants the S 0 multiline signal can only be resolved after methanol addition (Messinger et al 1997a). An ESEEM study employing 2 H-labeled methanol clearly showed that methanol (and ethanol) binds at-or at least very close to-the Mn 4 O x Ca cluster (Force et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several EPR and FTIR studies suggest that ammonia has one or two binding sites at the Mn 4 O x Ca cluster (for review see, Debus 1992;Hillier and Messinger 2005). At high enough concentrations ammonia inhibits O 2 evolution and alters the S 2 state EPR multiline signal (Haddy 2007). The possible competition between ammonia and methanol for binding sites at the water-splitting Mn 4 O x Ca cluster of photosystem II has been studied by two groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the limited knowledge about the accurate geometry of the Mn 4 Ca cluster, a direct correlation of the spec-troscopic data to structural changes of the cluster is difficult. The recent high resolution crystal structure from XRD reported by Umena et al (1) has provided a more precise geometry of the OEC structure with possibly limited effects from radiation damage (see below).…”
mentioning
confidence: 99%
“…Not only is this radiation damage a problem for PSII, but it also presents a challenge encountered in many other redox-active metalloenzymes [15][16][17][18]. Thus far, the geometric and electronic structural information of the intact Mn 4 CaO 5 cluster has been primarily addressed by spectroscopic methods [19][20][21][22], especially X-ray absorption (XAS) and emission spectroscopy (XES) techniques [14,[23][24][25]. Among these, XES is a powerful method for studying the charge and spin density and the ligand environment of the metal sites [26].…”
Section: Introductionmentioning
confidence: 99%